The Influence of Environmental, Social, Governance Disclosure and Profitability on Firm Value in the BEI Period 2017–2023 - Febrina Jayanti; Usep Syaipudin; Retno Yuni Nur Susilowati (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of disclosure of Environmental Social Governance and Profitability on the value of mining sector companies on the Indonesia Stock Exchange for the period 2017-2023. This type of research is quantitative based on secondary data. This research data uses mining sector companies listed on the IDX from 2017 to 2023 with a total sample of 12 companies. The sample was obtained using purposive sampling technique. Panel data regression analysis was performed using Eviews 12 in this study. This study found that Environmental disclosure and Social disclosure have no effect on firm value, while Governance disclosure and Profitability affect firm value, then Company Size has no effect on firm value as a control variable. Limitations in measuring the quality of ESG disclosures and focusing on one industry sector are important considerations for future research to expand data coverage and use a more comprehensive approach in evaluating the impact of ESG on firm value.